Are Risk Attitudes and Time Preferences Crucial Factors for Crop Diversification by Smallholder Farmers? - Arieska Wening Sarwosri; Oliver Mußhoff (Journal of International Development, 2020)
This study examines whether the decision of crop diversification for perennial crops is based on risk attitudes and time preferences. We conducted incentivised field experiments with farmers only cultivating rubber and those cultivating rubber and oil palm. We utilised Holt and Laury task and Coller and William task. We found that farmers who cultivate two crops are more risk-averse, indicating that they see crop diversification as a safer option for their farms. However, the discount rates of the two groups are not significantly different. These results provide relevant information for policymakers who intend to either encourage or discourage oil palm cultivation. 2020 The Authors. Journal of International Development published by John Wiley & Sons Ltd
Keywords: 300; crop diversification; oil palms; perennial crops; risk attitudes; rubber; time preference